131k views
0 votes
Solve the quadratic equation by completing the square.

3x2 - 6x - 4 = 0

User Vega
by
4.8k points

2 Answers

3 votes

Answer:

-0.53, 2.53 to the nearest hundredth.

Explanation:

3x^2 - 6x - 4 = 0

3(x^2 - 2) - 4 = 0

3 [ ( x - 1)^2 - 1] = 4

3(x - 1)^2 - 3 = 4

3(x - 1)^2 = 7

(x - 1)^1 = 7/3

x - 1 = +/- √(7/3)

x = +/- √(7/3) + 1

x = 2.53, -0.53.

User Sanah
by
5.3k points
1 vote

Answer:

The Answer is A x = 3 ± 21/3

Step-by-step explanation: I have tooken the test in usa test prep and this was the correct answer.

User Carl Anderson
by
5.4k points